ELECROMOTIVE FORCE OF LOW SPEED PERMANENT MAGNET GENERATOR WITH SKEWED POLE - TRIHATMAJA (NIM : 13204103); Pembimbing : Dr. Ir. Qamaruzzaman, WICAKSONO
Generator has a function to convert mechanical power into electrical power. The mechanical power in the form of torque is the input for generators. At low speed, input torque will decrease due to the inertia of the rotor and because of torque resistance, usually called cogging torque. Cogging torque produced by interaction the magnets on the rotor with generator stator core, especially when generator at no load condition. Cogging torque is reduced by skewing the magnet arrangement on the rotor. The magnetomotive force of the skewed pole, hence the elekctomotive force generated in the stator winding is analyzed by using the quasi 3D method. The emf is reduced compared to unskewed pole dependent on the degree of the skew.